Demokrasi Partisipatif Dalam Pembuatan Kebijakan Publik: Tantangan Dan Peluang Di Indonesia - Mozin, Sri Yulianty; Patuti, Vanda Imelda; Hasan, Hadidjah; Mahmud, Zubaidah; Sampara, Mohamad Prayuda (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
An increasing number of Indonesian public officials see participatory democracy as a way to make government decision-making more transparent, accountable, and plausible. But, many challenges remain in the way of fully implementing participatory democracy, including insufficient community capacity, knowledge disparity, and an overly bureaucratic system. In order to improve public participation in policymaking, this essay analyzes the main challenges of participatory democracy and proposes solutions. Using qualitative methodologies grounded in literature reviews and policy analyses, this study establishes that digital technology development, government decentralization, and public knowledge of participatory rights present strategic opportunities to promote participatory democracy in Indonesia. In order to address these challenges, this research proposes enhancing community capacity, enhancing the utilization of technology for public involvement, and introducing more inclusive policy reforms.